Revestimento cerâmico aplicado como barreira térmica em componentes automotivos - Moraes, Denison Angelotti (2018)
Automotive components are always in development, aiming to improve performance and quality, either by reducing costs, market need, increased sales and productivity or some new environmental or safety legislation. In the last years the environmental theme has gained interest and has become central to vehicles that use fossil fuels, especially Diesel oil, and must comply with new emission laws. For this, new engines and exhaust systems and gas filtration have been developed, such as catalytic converters. The upcoming legislation, called PROCONVE P8, restricts the values of nitrous oxides (NOx) and particulate matter to very low values. In order to achieve these values, the post-treatment system called the ATS (After Treatment System) was developed. In order for the process to reduce pollutants to be made within the ATS, the exhaust gases burned in the combustion process inside the engine must be between 450 and 550 ºC. The burned gases, or exhaust gases, are piped to the catalyst by metal tubing. In this work was proposed the use of 8% by weight (ZrO2-Y2O3) stabilized Zirconia oxide ceramic, known as YSZ (Ytria Stabilized Zirconia), or 8YSZ, known as TBC (Thermal Barrier Coating). The TBC was studied as a coating of exhaust pipe, through analytical calculation and CFD (Computer Fluid Dynamics). The results showed that the YSZ is a potential material for the studied application, as well as for applications where the thermal barrier theme is relevant.